2022
DOI: 10.1039/d2fo01379g
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnosis fiber : carbohydrate intake ratio and mortality of ovarian cancer: results from a prospective cohort study

Abstract: The association between the ratio of fiber to carbohydrate (F : C-R) and cancer mortality is not currently well-known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(58 reference statements)
0
3
0
1
Order By: Relevance
“…Previous evidence has indicated that healthy components of a pre-diagnosis diet were associated with better OC survival, raising the possibility of healthy dietary choices after diagnosis. [8][9][10][11][12][13][14][15][16] The colors of fruits and vegetables (FV) may serve as an indicator for their nutrient content, and may be used for grouping. 17 The colorful appearance of FV is attributed to the presence of phytonutrients that occur naturally and have pigmented properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has indicated that healthy components of a pre-diagnosis diet were associated with better OC survival, raising the possibility of healthy dietary choices after diagnosis. [8][9][10][11][12][13][14][15][16] The colors of fruits and vegetables (FV) may serve as an indicator for their nutrient content, and may be used for grouping. 17 The colorful appearance of FV is attributed to the presence of phytonutrients that occur naturally and have pigmented properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has indicated that healthy components of a pre-diagnosis diet were associated with better OC survival, raising the possibility of healthy dietary choices after diagnosis. 8–16…”
Section: Introductionmentioning
confidence: 99%
“…Patients included in this cross-sectional study were acquired from the OOPS (28), which is a prospective longitudinal cohort study of patients newly diagnosed with OC. Being approved by the Institutional Review Board of the Ethics Committee of Shengjing Hospital of China Medical University, Shenyang, China (2015PS38K), the OOPS was devoted to collecting clinical and lifestyle information and exploring their associations with cancer-related outcomes (29)(30)(31)(32)(33)(34). Patients recruited during the baseline survey were histologically confirmed OC diagnosis, with age between 18 and 79 years old.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Las propiedades tecnológicas de los productos alimenticios están relacionadas con las interacciones químicas entre las proteínas, los lípidos y la fibra con las moléculas de agua y aceite (Campos-Vega et al, 2018). El alto contenido de fibra en los alimentos a base de CPH aumenta la ingesta de alimentos y disminuye la digestibilidad aparente, debido a que el tránsito de los alimentos a través del tracto gastrointestinal se ve reducido por la presencia de este macronutriente (Liu et al, 2010).…”
Section: Resultados Y Discusionesunclassified